2015
DOI: 10.1103/physrevd.91.112009
|View full text |Cite
|
Sign up to set email alerts
|

Search forB++νγdecays with hadronic tagging using the full Belle data sample

Abstract: We search for the decay B + → + ν γ with + = e + or µ + using the full Belle data set of 772 × 10 6 BB pairs, collected at the Υ(4S) resonance with the Belle detector at the KEKB asymmetricenergy e + e − collider. We reconstruct one B meson in a hadronic decay mode and search for the B + → + ν γ decay in the remainder of the event. We observe no significant signal within the phase space of E sig γ > 1 GeV and obtain upper limits of B(B + → e + νeγ) < 6.1 × 10 −6 , B(B + → µ + νµγ) < 3.4 × 10 −6 , and B(B + → +… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 21 publications
8
19
0
Order By: Relevance
“…This determination satisfies the lower limit λ B > 238 MeV (at 90% C.L.) obtained by the Belle collaboration [45], which combines the search for B → γ ν with the theory prediction for its branching ratio [46,47]. It is worth recalling that this limit is a challenge for the lower values (λ B ∼ 200 − 250 MeV) preferred by the QCD factorization [51] and B-meson LCDAs for the B → π form factor and using a similar model for the B-meson DA as the Model I used here (see Appendix B.2).…”
Section: Numerical Input and Strategysupporting
confidence: 82%
See 1 more Smart Citation
“…This determination satisfies the lower limit λ B > 238 MeV (at 90% C.L.) obtained by the Belle collaboration [45], which combines the search for B → γ ν with the theory prediction for its branching ratio [46,47]. It is worth recalling that this limit is a challenge for the lower values (λ B ∼ 200 − 250 MeV) preferred by the QCD factorization [51] and B-meson LCDAs for the B → π form factor and using a similar model for the B-meson DA as the Model I used here (see Appendix B.2).…”
Section: Numerical Input and Strategysupporting
confidence: 82%
“…We refrain from replacing f + (s) by its model expression (40), since one may choose to use another model or a direct experimental determination of f + (s) inside the integral in Eq. (45). In deriving Eq.…”
Section: Resonance Models For B → Kπ Form Factorsmentioning
confidence: 99%
“…In order to perform the numerical analysis of the newly derived expressions for F V (n · p) and F A (n · p) in (4.12) and (4.13), we will proceed by specifying the nonperturbative models for the two-particle and three-particle DAs of the B-meson, determining the sum rule parameters and setting the hard and hard-collinear scales. Taking advantage of the new measurements of the partial branching fractions of B → γ ν from the Belle Collaboration [35], theory constraints of the inverse moment of the leading-twist DA φ + B (ω, µ) will be further addressed with the updated predictions for the B → γ form factors presented above.…”
Section: Numerical Analysismentioning
confidence: 99%
“…Since the factorization formula for the decay amplitude A(B − → γ ν) was established with the power counting scheme n · p ≡ 2E γ ∼ O(m b ), the phase-space cut on the photon energy needs to be introduced in the definition of the integrated decay rate 12) in order to facilitate the comparison of the experimental measurements from the Belle Collaboration [35] and the theoretical predictions displayed in figure 9. The main observations can be summarized as follows.…”
Section: Nlpll V2pmentioning
confidence: 99%
“…It can be observed that the integrated branching fractions BR(B → γ ν, E γ ≥ E cut ) grow rapidly with the decrease of the inverse moment due to the dependence of the two form factors on 1/λ B (µ 0 ) at leading-power in Λ/m b . Since the photon-energy cut E γ ≥ 1 GeV implemented in the Belle measurements [47] is not sufficiently large to perform perturbative QCD calculations of the B → γ form factors, we will not employ the experimental bound BR(B → γ ν, E γ ≥ E cut ) < 3.5 × 10 −6 with the full Belle data sample reported in [47] for the determination of λ B (µ 0 ) at the moment. Instead, we prefer to explore the solid theory constraints on the first inverse moment by comparing our predictions of the (partially) integrated branching fractions with the improved measurements at the Belle II experiment, with the tighter phase-space cut on the photon energy, thanks to the much higher designed luminosity of the SuperKEKB accelerator.…”
Section: Jhep05(2018)184mentioning
confidence: 99%